Identification of stress level and stress management (MSTRESS) by android mobile application / Nur Rasyidah Baharudin - Baharudin, Nur Rasyidah (2020)
Stress is a common psychological problem similar to many psycho-physical disorders. Most of applications created for mental health and which are now accessible to mobile users has grown in recent years. Some of current application have lack features such as identification of stress level that would greatly improve the functionality of the application. Therefore, the Perceived Stress Scale (PSS) has been assessed into the mobile application.